The Nazis, the Vatican, and the Jews of Rome - Gallo, Patrick J. 1937- (Purdue University Press, 2023)
On October 16, 1943, the Jews of Rome were targeted for arrest and deportation. The Nazis, the Vatican, and the Jews of Rome examines why?and more importantly how?it could have been avoided, featuring new evidence and insight into the Vatican?s involvement. At the time, Rome was within reach of the Allies, but the overwhelming force of the Wehrmacht, Gestapo, and SS in Rome precluded direct confrontation. Moral condemnations would not have worked, nor would direct confrontation by the Italians, Jewish leadership, or even the Vatican. Gallo underscores the necessity of determining what courses of actions most likely would have spared Italian Jews from the gas chambers. Examining the historical context and avoiding normative or counterfactual assertions, this book draws upon archival sources ranging from diaries to intelligence intercepts in English, Italian, and German. With antisemitism on the rise today and the last remaining witnesses passing away, it is essential to understand what happened in 1943. The Nazis, the Vatican, and the Jews of Rome grapples with this particular, awful episode within the larger, horrifying story of the Holocaust. Despite the inadequacy of memory, we must continue to attempt to make sense of the inexplicable.